2016
DOI: 10.1109/jstars.2016.2517118
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Weighted Dynamic Time Warping Method for Land-Use and Land-Cover Mapping

Abstract: A major recent trend in remote sensing research is the analysis of satellite image time series for land use and land cover monitoring and mapping. In this paper, we describe the Time-Weighted Dynamic Time Warping algorithm, which improves on previously proposed methods for land cover and land use classification. The method is based on the dynamic time warping method that measures similarity between two temporal sequences. We modified this method to account for seasonality of land cover types. The resulting alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(195 citation statements)
references
References 35 publications
3
183
0
9
Order By: Relevance
“…For the performance of different feature scenarios, the results indicated that the spectral features are fundamental for in-season crop classification, and temporal features extracted from high resolution time series significantly improves the classification accuracy relative to the case of using a single image, which is also consistent with the findings of the previous studies [55][56][57][58][59]. Ideally, each feature would provide extra information and improve classification accuracy.…”
Section: Discussionsupporting
confidence: 85%
“…For the performance of different feature scenarios, the results indicated that the spectral features are fundamental for in-season crop classification, and temporal features extracted from high resolution time series significantly improves the classification accuracy relative to the case of using a single image, which is also consistent with the findings of the previous studies [55][56][57][58][59]. Ideally, each feature would provide extra information and improve classification accuracy.…”
Section: Discussionsupporting
confidence: 85%
“…Faced with the challenge of systematic land cover and land use mapping on a large scale, the images provided by the MODIS sensor (Moderate Resolution Imaging Spectroradiometer) [19], (e.g., [20]), combined with new classification algorithms (e.g., [21]), made possible highly accurate and recurring representations of the Earth's surface (e.g., [22,23]). Specifically, this work uses MODIS data and a novel approach to produce annual pasture area maps for the entire Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these techniques are based on a reduction dimension which implies a loss of information. To address this issue, new techniques, such as Dynamic Time Warping approaches with temporal weights, were successfully tested to classify land cover classes including single and double cropping systems, based on shape matching of MODIS EVI time series [69]. Bailly et al [70] implemented a Dense Bag-of-Temporal-SIFT-Words approach, which involves representing vegetation index time series in sequences of local features, such as peaks and constant growth.…”
Section: Sequential Croppingmentioning
confidence: 99%